Comment on Lone et al. Phylogenetic Relationships in Earthworm Megascolex Species (Oligochaeta: Megascolecidae) with Addition of Two New Species. Diversity 2022, 14, 1006 - Sasankan Prasanth Narayanan; Rahul Paliwal; Ambattu Paili Thomas; Jatinder Mohan Julka (Diversity)
Currently, on a global scale, integrated taxonomical works, by incorporating the molecular approach and traditional taxonomic methods have gained acceptance. Recently, Lone et al. (Diversity 2022, Phylogenetic Relationships in Earthworm Megascolex Species (Oligochaeta: Megascolecidae) with Addition of Two New Species) studied eleven Megascolex species (including two new species) from the Western Ghats biodiversity hotspot region of the Kerala state, India, by incorporating the integrated methods. The analysis of the results provided in Lone et al. indicated several discrepancies and shortcomings. They have overlooked or incorrectly described many key characters used in the Megascolex species identification and provided faulty figures. Apart from these, the paper had many factual as well as systematic errors. In this comment, based on the data provided by Lone et al., we critically reviewed their work, citing the errors and defects so as to help them to avoid similar issues in their future works and to obviate further confusions in the field of earthworm taxonomy.